Lagerstroemia reginae Roxb. - an Ideal Host Supporting Orchid Species of Barak Valley, Southern Assam - Bhattacharjee, B.; Dutta, B. K. (Indian Forester, 2009)
A study was carried out to investigate the ideal host plants for orchid diversity of Southern Assam. Five selected commonly available species of the valley were chosen in the study by Braun Blanquet cover abundance scale method. After analysis, Lagerstroemia reginae Roxb. has been observed to be the most suitable host plant of orchids followed by others, in three Reserve Forests where the study was carried out.